Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1136/bmjopen-2020-038870
|View full text |Cite
|
Sign up to set email alerts
|

Impact of allergic rhinitis on the day-to-day lives of children: insights from an Australian cross-sectional study

Abstract: Study design and objectiveCross-sectional, observational survey to describe the impact of allergic rhinitis (AR) on Australian children (2 to 15 years).MethodsParticipants (n=1541), parents of children aged 2 to 15 years, provided information on behalf of themselves and one eligible child in their household using a custom-built online questionnaire. Children were allocated to case (AR) or control (No AR) analysis groups based on a validated screening questionnaire.Statistical methodsThe study sample was strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…As expected, these studies show impacts on QOL in this population. More surprisingly, they show impacts on parental QOL as well 1064–1067 . In one study, parents overestimate their children's QOL 1068 .…”
Section: Allergic Rhinitis Disease Burdenmentioning
confidence: 98%
“…As expected, these studies show impacts on QOL in this population. More surprisingly, they show impacts on parental QOL as well 1064–1067 . In one study, parents overestimate their children's QOL 1068 .…”
Section: Allergic Rhinitis Disease Burdenmentioning
confidence: 98%
“…Compared with nonasthmatic children, children with asthma scored lower on physical and emotional functioning, but not on social functioning 10,11 . Poorer emotional and physical outcomes were also observed in children with allergic rhinitis 12 …”
Section: Introductionmentioning
confidence: 96%
“…10,11 Poorer emotional and physical outcomes were also observed in children with allergic rhinitis. 12 Although the impact on HRQOL has been studied extensively, studies have mainly focused on children diagnosed with a single allergic disease. Recent research has found that multiple chronic health conditions are correlated with internalizing symptoms such as anxiety and depression in children.…”
mentioning
confidence: 99%
“…Allergic rhinitis (AR) is a highly prevalent chronic disease that causes symptoms in the upper airway (e.g. nasal pruritus and congestion, sneezing) and red itchy eyes, resulting in physical discomfort, sleep disturbances, impaired school performance, lower work productivity and in general an impaired quality of life (QoL) 1–6 . AR is recognized as a major risk factor for the development of allergic asthma (AA) 7,8 .…”
Section: Introductionmentioning
confidence: 99%